IMPROVING THE PROFESSIONAL TRAINING OF FUTURE ENGINEERS BASED ON THE CLUSTER APPROACH - Sirojiddinova Iroda Mаhammadovna (Journals Park Publishing, 2022)
This scientific article discusses the systematic analysis of the process of improving the professional training of future engineers, the meaning of the word "cluster", its popularity and practical significance in pedagogy. The concept of "cluster technology in the improvement of professional career" is not only introduced into the Uzbek education system, but also introduced into the education system in foreign countries on the basis of reliable sources.
Keywords: Professional training; cluster; collaboration